2000
DOI: 10.1067/mcp.2000.110456
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine decreases platelet serotonin storage and platelet function in human beings

Abstract: Paroxetine substantially decreases intraplatelet serotonin content and thereby reduces platelet plug formation under shear stress, and responsiveness to thrombin receptor activating peptide-induced platelet activation. Further studies will reveal whether these pharmacodynamic effects can be exploited for treatment of thrombotic artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
169
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(183 citation statements)
references
References 35 publications
9
169
0
5
Order By: Relevance
“…Antidepressants that prevent the uptake of serotonin into platelets may thereby inhibit the only mechanism for platelet storage of serotonin. 4 All of the high-affinity SSRIs represented in the present study have been shown to reduce platelet aggregation. 5,[13][14][15] We know of no studies that have suggested altered platelet activity attributed to the other antidepressants with low or moderate serotonin transporter affinity; however, one study demonstrated no effect of nortriptyline on platelet activity.…”
Section: Potential Role Of Serotonin Reuptake Inhibitors In Preventiomentioning
confidence: 99%
See 1 more Smart Citation
“…Antidepressants that prevent the uptake of serotonin into platelets may thereby inhibit the only mechanism for platelet storage of serotonin. 4 All of the high-affinity SSRIs represented in the present study have been shown to reduce platelet aggregation. 5,[13][14][15] We know of no studies that have suggested altered platelet activity attributed to the other antidepressants with low or moderate serotonin transporter affinity; however, one study demonstrated no effect of nortriptyline on platelet activity.…”
Section: Potential Role Of Serotonin Reuptake Inhibitors In Preventiomentioning
confidence: 99%
“…1,2 A genetic polymorphism of the serotonin transporter (the only mechanism for serotonin uptake into platelets) causes increased serotonin uptake and is associated with an increased risk of MI. 3 Antidepressants, particularly the selective serotonin reuptake inhibitors (SSRIs) with high affinity for the serotonin transporter, attenuate platelet activation by depleting serotonin storage 4 and have been shown to decrease platelet activity in patients with coronary artery disease. 5 The antiplatelet effects of SSRIs, most of which have high affinity for the serotonin transporter, have been implicated in an increased risk of gastrointestinal bleeding 6 and lower risk of MI among users of SSRIs.…”
mentioning
confidence: 99%
“…In studies performed in human beings all SSRIs have consistently shown a drastic decrease in platelet serotonin content after several weeks of treatment reaching levels around or below 10% of the pretreatment serotonin levels (Wagner et al 1990;Mück-Seler et al 1991;Narayan et al 1998;Hergovich et al 2000;Javors et al 2000) (fig. 1).…”
Section: Pharmacology Of Ssris On Platelets and The Biological Plausimentioning
confidence: 99%
“…1 During treatment with SSRIs, the intraplatelet serotonin content is reduced as a result of inhibition of the serotonin reuptake mechanism. 5 Bleeding complications during SSRI treatment could be due to an impaired hemostatic response. Conversely, it is conceivable that SSRIs might reduce the risk of thrombus formation, although the effect of SSRI exposure on the risk of ischemic stroke has not been previously studied.…”
mentioning
confidence: 99%